The Influence of the Digital Word on Student’s Motoric - Chindy Octa Vijjani; Hudaidah Hudaidah (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2021)
Technology is a science that provides facilities or systems that aim to provide convenience and comfort to mankind. Technology is the development of science, especially in the world of education. With the development of technology that can be used by mankind, especially for students. There are so many benefits of technological developments that can be obtained, such as: can add information, facilitate access to learning, and so on. But behind the benefits that have been obtained, of course there are tribulations that follow. Many students misuse this technological development so that it makes students experience a decline in learning, stunted motor development due to misuse of technology.